Perceptions of Students at Andalas University's Payakumbuh Campus Regarding the Security of Academic Information Systems - Yindrizal (PT Inovasi Pratama Internasional, 2024)
Higher Education is one of the public service providers that wants to provide the best service to internal and external parties who need information, namely by utilizing academic information systems. The use of academic information systems is prone to data and information crimes, which are problems experienced by many system users and this also occurs in Indonesia. The method in this study uses a qualitative description method in this study and data collection is obtained using triangulation techniques. The results of the study, that it is necessary to improve information security from various threats, thus ensuring the security of valuable information assets. Information security using The International Organization for Standardization (ISO)/IEC 27001. In addition, it is also necessary to perform two-factor authentication which adds a two-step verification process to access the account.